Emerging Trends In Green Marketing - G Brindha; J. Bhavani; B. Karthik (International Journal of Psychosocial Rehabilitation, 2020)
he concept of environmental protection and green consumption has emerged as important issues for concern among the public. Green marketing comprises abroad range of actions containing product variation, variations to the, adjusting advertising, packaging alterations and production process. The concept of Green and eco-friendly has become currently an integrated part of the marketing literature. Major corporate have evolved with a new perspective of launching green marketing concept in their business strategy. These organizations have merged environment tprotection and waste reduction in their policy. The role of Government in maintaining the purity of environment is clearly understood through the laws and regulations that are imposed on the business firms towards this aspect. At present to survive and grow in the competitive businesss cenario organizations has to implement various environment protection policies in their operations. Hence it is mandatory for the firms globally to use the resources competently and avoiding wastage. Green marketing is predictable as the arcade for informally accountable produces is cumulative erapidly in the society. The contemporary article deliberates the importance of green marketing from the public and corporate perspectives respectively. This article also attempts to identify the occasions and experiments in green marketing.